The Effect of Health Promotion of Common Cold Massage Skills on The Duration of Healing of ARI (Common Cold) in Toddlers - Laili Fajriyah; Reny Retnaningsih (KHD Production, 2026)
Acute respiratory infections (ARIs), particularly the common cold, account for 30–40% of toddler consultations in primary care settings in Indonesia. Nonpharmacological complementary therapies are urgently needed to reduce disease burden and antibiotic misuse. To evaluate the impact of a 2-day parent-administered